Assessing the Timemania Lottery as a sports public policy - Dirceu Santos Silva; Bruno Modesto Silvestre; Silvia Cristina Franco Amaral (Journal of Physical Education (Maringá), 2020)
This paper analyses the main results of Timemania as a sports public policy based on the efficiency, efficacy and social effectiveness principles. A descriptive-analytical research with qualitative approach was conducted through the analysis of contents from laws and official reports. Results suggest that the Timemania lottery was neither efficacious nor efficient, as it did not achieve the initial goals as to its revenues and debt payment for clubs. Timemania was not effective and did not significantly impact sports development. Finally, it is possible to conclude that Timemania, as a regulatory policy, fulfills the sole role of ensuring financial injection for major Brazilian football clubs.